2019
DOI: 10.1016/j.jenvp.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of normative prompts and norm support cues in promoting light-switching behavior: A field study

Abstract: Positive descriptive norm cues, as well as injunctive norm messages, can enhance the occurrence of turning off the lights in unoccupied rooms. However, the impact of descriptive norm messages as well as the role of congruent or conflicting normative cues have not yet been verified in this particular context. Two field experiments compared the effectiveness of three experimental prompts (injunctive norm vs. descriptive norm vs. request only) on behavioral measures (Study 1, N = 710; Study 2, N = 1,792) of light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 84 publications
1
17
0
Order By: Relevance
“…To increase the external validity of our results, targeting a broader and more diverse population would be recommended. Various types of prompts (e.g., Bergquist and Nilsson, 2016;Leoniak and Cwalina, 2019) could also be tested in interaction with attitudes, as the framing of a message could have a different impact depending on initial attitudes. Notably, the fact that the prompt only mentions the behavior (e.g., "Please turn off the lights") versus refers to the environment as an argument to do the behavior (e.g., "Please turn off the lights to protect the environment") does probably change the influence of attitudes, the former being even less susceptible to be influenced by the level of environmental attitudes of the person.…”
Section: Future Studiesmentioning
confidence: 99%
“…To increase the external validity of our results, targeting a broader and more diverse population would be recommended. Various types of prompts (e.g., Bergquist and Nilsson, 2016;Leoniak and Cwalina, 2019) could also be tested in interaction with attitudes, as the framing of a message could have a different impact depending on initial attitudes. Notably, the fact that the prompt only mentions the behavior (e.g., "Please turn off the lights") versus refers to the environment as an argument to do the behavior (e.g., "Please turn off the lights to protect the environment") does probably change the influence of attitudes, the former being even less susceptible to be influenced by the level of environmental attitudes of the person.…”
Section: Future Studiesmentioning
confidence: 99%
“…Moreover, some other studies have explored whether different kinds of norms, such as subjective/descriptive/injunctive norms, affect specific PEBs in different ways (Zhang et al, 2018b ; Choi et al, 2015 ;Leoniak & Cwalina, 2019 ;Oceja & Berenguer, 2009 ). In addition, some scholars focused on how to effectively carry out green marketing activities and further cultivate residents’ sustainable consumption behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Injunctive and descriptive norms represent distinct sources of motivation and should have separate influences on a given behavior (Cialdini et al, 1990; Schuster et al, 2016; Smith et al, 2012). Although some previous social marketing studies have used social norms as a unidimensional construct (Onel, 2017; Russell-Bennett et al, 2018), there is empirical research evidence that descriptive and injunctive norms have independent and distinct impacts on intentions and behavior (Cialdini et al, 1990; Geiger et al, 2019; Leoniak & Cwalina, 2019; Smith et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning waste separation actions specifically, an extended theory of planned behavior model developed by Xu et al (2017) showed that gender and age significantly moderate the relationship between the behavioral intention and its antecedents. Specific to normative influence, Leoniak and Cwalina (2019) established that women comply equally with injunctive and descriptive norms, while men are less compliant with descriptive norms than women.…”
Section: Literature Reviewmentioning
confidence: 99%